(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Staphylococcus aureus is one of the most common causes of skin and soft tissue infections (SSTIs). Methicillin resistant staphylococcus aureus (MRSA) is the resistant to all penicillinase stable penicillins, thus the acronym MRSA is still commonly used even though methicillin is no longer the agent of choice for treatment of community associated MRSA infection. Objective of this study was to determine prevalence of Staphylococcus aureus and methicillin resistance with antimicrobial susceptibility profile. This was a retrospective study (part of MSc dissertation) held for 6 months in Safdarjung hospital, New Delhi. Samples were collected from the dermatology out-patient department of VMMC Safdarjung hospital, New Delhi, from patients with a variety of skin and soft-tissue lesions. The specimens were transported in sterile, leak-proof containers to the bacteriology laboratory. Samples were inoculated on blood and mac-conkey agar plates and confirmed through colony morphology, gram staining and biochemical test. MRSA -Screen was done through latex agglutination test for the detection of PBP2a present in isolates of Staphylococcus aureus in MRSA. During the study period, samples were collected from total 100 patients and result of this study conclude that in patients with primary SSTIs, can be considered as preferred first line systemic therapeutic agents and the first choice of topical therapy for primary staphylococcal SSTIs is mupirocin.